Fans Make Art: Authoring and Creativity in the Production of Fanvideos - de Souza-Leão, André Luiz Maranhão; Moura, Bruno Melo; Santana, Italo Rogerio Correia de; Nunes, Walber Kaíc da Silva; Henrique, Vitor de Moura Rosa (Revista de Negócios, 2019)
The research aims to analyze how Brazilian produce fanvideos based on successful pop culture franchises. For such, assumes that fans are prosumers of pop culture in a context of participatory culture and that fanvideos are user-generated content propitiated by Web 2.0 technologies. A total of 257 fanvideos posted between April 2006 and February 2018 were analyzed through Interpretive Content Analysis. Five types of fanmade productions were identified: fandub, fanart, fan animation, fan music and fanfiction. Such production demonstrates that fanvideos reveal the fans' desire to make art, what occurs both as a way for the fans relate to the franchises they admire, as well as to express themselves based on them. By doing this, they wide the scope and the narrative possibilities of the franchises through intra- and inter-textualities in relation to the universe of pop culture and their own daily experiences. The research presents an original approach to user-generated content in association to fan production and the notion of prosumption. As limitation, the study is delimited to the Brazilian production of fanvideos. Future similar research could be carried out in other countries, as well as regarding other fan productions.